2022
DOI: 10.1002/cncy.22615
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an artificial intelligence algorithm for assisting the Paris System in reporting urinary cytology: A pilot study

Abstract: BACKGROUND:The Paris System for Reporting Urinary Cytology (TPS) has been shown to improve bladder cancer diagnosis. Advances in artificial intelligence (AI) may assist and improve the clinical workflow by applying TPS in routine diagnostic services. METHODS: A deep-learning-based algorithm was developed to identify urothelial cancer candidate cells using whole-slide images (WSIs). In the testing cohort, 131 urine cytology slides were retrospectively retrieved and analyzed using this AI algorithm. The authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Using mixed-methods, Calisto et al 300 patients found that AI assistance increased detection of adenomas and serrated polyps during colonoscopy in comparison to historical controls, but the findings were not statistically significant. Ou et al [24] demonstrated that AI-assisted analysis of urine cytology outperformed the conventional method, with improved sensitivity (92% vs. 87%) and NPV (97% vs. 95%). Nasir-Moin et al [25] showed that AI for interpretation of 100 colorectal polyp samples significantly improved pathologists' classification accuracy compared with standard microscopic assessment (74% to 81%).…”
Section: Cancermentioning
confidence: 99%
“…Using mixed-methods, Calisto et al 300 patients found that AI assistance increased detection of adenomas and serrated polyps during colonoscopy in comparison to historical controls, but the findings were not statistically significant. Ou et al [24] demonstrated that AI-assisted analysis of urine cytology outperformed the conventional method, with improved sensitivity (92% vs. 87%) and NPV (97% vs. 95%). Nasir-Moin et al [25] showed that AI for interpretation of 100 colorectal polyp samples significantly improved pathologists' classification accuracy compared with standard microscopic assessment (74% to 81%).…”
Section: Cancermentioning
confidence: 99%
“…Utilizing this approach, several studies were identified; Cochrane Library (47), PubMed® (26), Scopus™ (241), Google Scholar (3330) and Web of Science™ (2). Duplicate results, articles or audits not published in peer-reviewed journals were excluded.…”
Section: Appli C Ati On Of Ai In De Tec Ti On and T Yping Of Fung Us ...mentioning
confidence: 99%
“…There have been multiple efforts to digitize TPS by incorporating digital pathology methods into the analysis of urine cytology slides. [6][7][8][9][10][11][12][13][14] Many of these efforts hinge on whole-slide imaging to scan urine cytology slides at high resolution to allow for digital image analysis. Some early studies used the manual annotation of urothelial cells to better quantify TPS cytomorphologic criteria; the N/C ratio has been the most studied criterion using these methods.…”
Section: Introductionmentioning
confidence: 99%
“…There have been multiple efforts to digitize TPS by incorporating digital pathology methods into the analysis of urine cytology slides 6–14 . Many of these efforts hinge on whole‐slide imaging to scan urine cytology slides at high resolution to allow for digital image analysis.…”
Section: Introductionmentioning
confidence: 99%